Hepatitis B virus-infected hepatocytes promote the secretion of collagen VI to the extracellular matrix - Alessia Virzì; Zakaria Boulahtouf; Julien Moehlin; Lea Girard; Laura Meiss-Heydmann; Charlotte Bach; Emma Gerges; Sarah C. Durand; Marine A. Oudot; Armando A. Roca Suarez; Oliver Popp; Evelyn Ramberger; et al. (Scientific Reports)
Abstract Chronic hepatitis B virus (HBV) infection is a global health problem as it is the major cause of liver fibrosis and its complications cirrhosis and hepatocellular carcinoma. The role of virus–host interactions in liver fibrosis and progression to cancer remains poorly understood. Here we show that HBV infection of permissive cells trigger pathways relevant for extracellular matrix (ECM) remodeling, which is a hallmark of liver fibrosis. We demonstrate that collagen VI (ColVI) is secreted from infected cells and induces a profibrotic phenotype in patient-derived myofibroblasts and identified HBV-induced AKT signaling as a driver of ColVI expression in HBV-infected cells. Consistently, ColVI is upregulated in the liver of HBV patients with fibrosis. Our results suggest a role of ColVI as a driver of HBV-associated liver disease and highlight the potential of ColVI as a biomarker candidate and therapeutic target in HBV-infected patients.